Spacesuit Textiles from Extreme Fabric Materials: Aromatic Amide Polymer and Boron Nitride Nanotube Composite Fiber for Neutron Shielding and Thermal Management - Ryu, Ki-Hyun; Kang, Minsung; Kim, Jungwon; You, Nam-Ho; Jang, Se Gyu; Jeong, Kwang-Un; Ahn, Seokhoon; Kim, Dae-Yoon (Springer Nature, 2024)
Space exploration provides unparalleled opportunities for unraveling the mysteries of our origins and exploring planetary systems beyond Earth. Long-distance space missions require successful protection against significant radiation exposure, necessitating the development of effective radiation shielding materials. This study developed aromatic amide polymer (AAP) and boron nitride nanotube (BNNT) composite fibers using lyotropic liquid crystal (LLC) and industrially viable wet-spinning processes. The uniaxially oriented 1D composite fibers provide the necessary continuity and pliability to fabricate 2D macroscopic textiles with low density (1.80 g cm-3), mechanical modulus (18.16 GPa), and heat stability (up to 479 degrees C), while exhibiting the improved thermal neutron absorption cross-section with thermal neutron-shielding performance (0.73 mm-1). These composite textiles also show high thermal conductivity (7.88 W m-1 K-1) due to their densely packed and uniaxially oriented structures. These enhanced characteristics render the fibers a highly promising material for space applications, offering robust protection for both astronauts and electronics against the dual threats of radiation and heat.